2012
DOI: 10.5660/wts.2012.1.4.044
|View full text |Cite
|
Sign up to set email alerts
|

Herbicidal Activity of Essential Oil from Amyris (Amyris balsamifera)

Abstract: ABSTRACT. The objective of this study was to know the herbicidal activity of the essential oil from amyris (Amyris balsamifera). In a seed bioassay experiment, the amyris essential oil inhibited the growth of rapeseed (Brassica napus) by fifty percent at 8.8 µg g . And in a greenhouse experiment, sorghum, barnyard grass and Indian jointvetch, which was applied in above-ground parts, with the amyris essential oil at 4,000 µg ml -1 showed visual injuries of 90, 70, and 70, respectively (0, no damage; 100, total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Malik (2019) indicated sabinene 5.7%, α-phelandrene 17.6%, limonene 56%, and elemol 6.3% as the main components of the essential oil C. luzonicum. Silva et al (2012) identified limonene, β-Cymene, β-fellandren, αphellandren and β-pinene as the main components of C. luzonicum essential oil.…”
Section: Chemical Composition Of Essential Oilsmentioning
confidence: 99%
“…Malik (2019) indicated sabinene 5.7%, α-phelandrene 17.6%, limonene 56%, and elemol 6.3% as the main components of the essential oil C. luzonicum. Silva et al (2012) identified limonene, β-Cymene, β-fellandren, αphellandren and β-pinene as the main components of C. luzonicum essential oil.…”
Section: Chemical Composition Of Essential Oilsmentioning
confidence: 99%
“…(Bainard and Isman, 2006;Kim et al, 2008;Tworkoski, 2002;Yun et al, 2012) Means are based on data from three replicates. a The herbicidal activity was determined by visual injury 7 days after the application of the essential oil.…”
Section: 제초 활성 검정mentioning
confidence: 99%